Top 10 of everything : 2018 - Terry, Paul. (--London: Octopus Publishing, 2017)
1. Animal kingdom. -2. Forces of nature. --3. Humankind. --4. Sports. --5. Epic structures. --6. Mechanical creations. --7. Outer space. --8. Video games. --9. Music. --10. Movies & TV.
Includes index.
Keywords: Curiosities and wonders; World records -- Miscelllanea